AGROY: creating value through smart farming. Issue 3 (13th December 2019) - Singh, Ramendra; Kumar, Jitender; Nayak, Avilash
Abstract : Learning outcomes: This case study outlines the marketing, strategic and organizational issues facing the ever-expanding agri-inputs market in India, through the perspective of Agroy – an agri-products company. This case can be used to assist in the teaching courses such as marketing management, rural marketing, business strategy, operations and logistics management, among others, for students of MBA or other specialized courses in management. The case has been developed to make students aware and to understand the arduous nature of setting up a company catering to the huge Indian agri-inputs market. This case delves into the complexities of marketing in rural India that is characterized by low technological awareness, low volumes of digital transactions and immense language barriers. The Indian agricultural market is huge and has undergone a considerable amount of change owing to competition among multinational companies and traditional local micro-retailers. This case discusses the various challenges faced by multinational companies in entering India and how they need to strategize to modify their Western model of a distribution channel which faces huge challenges when put to test in India. Specific learning outcomes include: the case study would help students to comprehend the new business strategies that an MNC could adopt in emerging markets. Some companies work on changing traditional and conventional value chains of activities to fit the emerging market customer's best and hence companies needs to figure out a unique business model to compete in emerging markets. This case study gives readers the opportunity to think about strategy in an uncertain environment. The case illustrates the challenges associated with innovating new business ideas that would help the company serve a greater number of people from a diverse background. It highlights the importance of thinking about real options, a portfolio of projects and the type of organizational structure required to tackle the uncertainties associated with foreign companies aiming to enter the Indian market. It also explores marketing and distribution issues – which are the type of customers to target and which are the suitable geographic areas with suitable linguistic compatibility in which there shall be ease in doing business. Finally, it is an avenue for students to think about the changes necessary throughout the distribution channel to successfully implement and commercialize a project in rural India. The case is intended to work well as a learning tool for strategy implementation where uncertainty is inherent and as an application to lectures on real options and risk or for discussions related to marketing and distribution channels and its challenges. Case overview/synopsis: The Indian agricultural market plays an important role in India's economy having a staggering 58 per cent of rural households depending on it as the principal means of livelihood. However they have very small landholdings, and hence, they find it difficult to order either large quantities or in bulk, as a result of which the cost of agricultural inputs gets enhanced. Agroy, an MNC, is one of the many companies that have stepped in to bridge this gap by trying to tap into the huge agricultural market. Agroy aspires to be the "UBER of agriculture." Agroy is a cloud-based buying platform for farmers to buy agri-inputs efficiently at scale and at the best price from around the world. With big data and smart farming, the company aims to enhance farm sustainability and productivity. Agroy's competitors like Agro Star and Big Heart also have similar business models and hence the competition is stiff. The three debatable questions that the case poses are: Will Agroy be able to shatter the age-old loyalty that Indian farmers have toward local retailers and other Indian companies that have an existing strong foothold in the market? Will similar distribution models as practiced in developed Western countries work in India, given the distribution challenges in deep rural Indian hinterland? Will Agroy be able to create sustainable business models by marketing agri-inputs at low prices in India? Complexity academic level: MBA in courses such as entrepreneurial marketing, strategic marketing, agricultural marketing. Supplementary materials: Teaching notes are available for educators only. Please contact your library to gain login details or email support@emeraldinsight.com to request teaching notes. Subject code: CSS 8: Marketing.